Clinicopathologic characteristics and therapeutic responses of Chinese patients with non‐small cell lung cancer who harbor an anaplastic lymphoma kinase rearrangement. Issue 3 (8th August 2015) - Fu, Sha; Wang, Hai‐Yun; Wang, Fang; Huang, Ma‐Yan; Deng, Ling; Zhang, Xiao; Ye, Zu‐Lu; Shao, Jian‐Yong
Abstract: Introduction: The rearrangement of the anaplastic lymphoma kinase ( ALK ) gene accounts for approximately 1%–6% of lung adenocarcinoma cases and defines a molecular subgroup of tumors characterized by clinical sensitivity to ALK inhibitors such as crizotinib. This study aimed to identify the relationship between ALK rearrangement and the clinicopathologic characteristics of non‐small cell lung cancer (NSCLC) and to analyze the therapeutic responses of crizotinib and conventional chemotherapy to ALK rearrangement in NSCLC patients. Methods: A total of 487 lung cancer patients who underwent testing for ALK rearrangement in our department were included in this study. ALK rearrangement was examined by using fluorescence in situ hybridization (FISH) assay. Results: Among the 487 patients, 44 (9.0%) were diagnosed with ALK rearrangement by using FISH assay. In 123 patients with adenocarcinoma who were non‐smokers and of a young age (≤58 years old), the frequency of ALK rearrangement was 20.3% (25/123). Short overall survival (OS) was associated with non‐adenocarcinoma tumor type ( P = 0.006), poorly differentiated tumors ( P = 0.001), advanced‐stage tumors ( P < 0.001), smoking history ( P = 0.008), and wild‐type epidermal growth factor receptor ( EGFR ) ( P = 0.008). Moreover, patients with poorly differentiated and advanced‐stage tumors had a shorter time to cancer progression compared with those with well differentiated ( P = 0.023) and early‐stage tumors ( P = 0.001), respectively. Conclusions: ALK ‐rearranged NSCLC tends to occur in younger individuals who are either non‐smokers or light smokers with adenocarcinoma. Patients with ALK rearrangement might benefit from ALK inhibitor therapy.